2014
DOI: 10.1152/ajpendo.00534.2013
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled estrogen receptor 1 mediates relaxation of coronary arteries via cAMP/PKA-dependent activation of MLCP

Abstract: Yu X, Li F, Klussmann E, Stallone JN, Han G. G proteincoupled estrogen receptor 1 mediates relaxation of coronary arteries via cAMP/PKA-dependent activation of MLCP. Am J Physiol Endocrinol Metab 307: E398 -E407, 2014. First published July 8, 2014 doi:10.1152/ajpendo.00534.2013.-Activation of GPER exerts a protective effect in hypertension and ischemia-reperfusion models and relaxes arteries in vitro. However, our understanding of the mechanisms of GPER-mediated vascular regulation is far from complete. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 78 publications
(95 reference statements)
5
59
0
Order By: Relevance
“…The mechanism of GPER-mediated vascular relaxation is, however, far from clear. As a typical G-protein-coupled receptor, GPER has been reported to interact with Gs, and thereby activate adenylyl cyclase and increase cAMP production in GPER-transfected HEK293 cell plasma membrane extracts and human CASMCs [9, 10]. Our recent work has demonstrated that cAMP/PKA signaling is involved in GPER-mediated relaxation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of GPER-mediated vascular relaxation is, however, far from clear. As a typical G-protein-coupled receptor, GPER has been reported to interact with Gs, and thereby activate adenylyl cyclase and increase cAMP production in GPER-transfected HEK293 cell plasma membrane extracts and human CASMCs [9, 10]. Our recent work has demonstrated that cAMP/PKA signaling is involved in GPER-mediated relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work has demonstrated that cAMP/PKA signaling is involved in GPER-mediated relaxation. In human and porcine CASMCs, GPER activation increased cAMP production and activated PKA activity, which in turn, phosphorylated RhoA and thus, inhibited RhoA activity, resulting in activation of the myosin light chain (MLC) phosphatase (MLCP) and dephosphorylation of MLC [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the cAMP/PKA pathway is activated by AGEs in diabetes [36]. Moreover, the cAMP/PKA pathway is widely recognized to regulate aortic SM contraction [37,38]. In gastric SMCs and intact aorta, PKA-mediated phosphorylation of IP 3 R3 decreases the number of binding sites for IP 3 on IP 3 R3 and thus attenuates IP 3 R3-mediated Ca 2+ release [29].…”
Section: Discussionmentioning
confidence: 99%
“…In hypertension and ischemia--reperfusion models activation of GPER is protective as it relaxes arteries. Inhibition of AKAP--PKA interactions with FMP--API--1 attenuated the effect of GPER activation on coronary artery relaxation by a mechanism involving activation of myosin light chain phosphatase and inhibition of a RhoA pathway [247].…”
Section: Small Moleculesmentioning
confidence: 94%
“…This conservation also hampers the development of peptidomimetics and small molecules for inhibition of specific AKAP--PKA interactions. The first peptidomimetics [6,153,220] and a first small molecule, FMP--API--1, for the non--selective disruption of AKAP--PKA interactions are available [36,247]. There are hints that allosteric sites such as the RI Specifier Region (RISR) in D--AKAPs [6] and a region C--terminally from the D/D domain of RII [36] are involved in AKAP--PKA interactions.…”
Section: Summary Conclusion and Outlookmentioning
confidence: 99%